Plato and the English Romantics - Douka-Kampitoglou, Aikaterinē, 1940- (Routledge library editions. Plato, 2013)
This book tackles the problematic relationship between Platonic philosophy and Romantic poetry, between the intellect and the emotions. Drawing on contemporary critical theory, especially hermeneutics and deconstruction, the author shows that a dialogue between thinking and poetizing is possible. The volume yields many new insights into both Platonic and Romantic texts and forms an important work for scholars and students of Greek philosophy, Romantic literature and critical theory.